Presurgical rehabilitation program for patients with symptomatic lumbar spinal stenosis: A pilot randomized controlled trial protocol. Issue 4 (22nd December 2022) - Bakaa, Nora; Gross, Douglas P.; Carlesso, Lisa C.; MacDermid, Joy; Thomas, Kenneth; Slomp, Florence; Rushton, Alison; Miciak, Maxi; Smeets, Rob; Rampersaud, Raja; Nataraj, Andrew; Drew, Brian; et al.
ABSTRACT: Background: Symptomatic lumbar spinal stenosis (SLSS) is the most common diagnosis associated with spine surgery for those over the age of 55 years. There is a lack of quality research on the effectiveness of prehabilitation on pain, function, and quality of life in patients undergoing surgery for SLSS. This pilot randomized controlled trial (RCT) will evaluate the feasibility of an eHealth prehabilitation program for individuals undergoing SLSS surgery, and an embedded longitudinal qualitative study explores the perioperative patient experience and recovery trajectory. Methods: Participants ( n = 60) undergoing spine surgery for LSS will be randomized into the 8-week electronic health (eHealth) prehabilitation program or minimal intervention. The prehabilitation program will be delivered virtually using synchronous (one-on-one) and asynchronous (independent) sessions by an experienced clinician, consisting of motivational interviewing, exercise (graded activity), education, peer support groups, and a 6-week booster session. Participants in the minimal care group will receive usual care and will have access to educational videos. Primary outcomes will include (1) recruitment, (2) patient adherence, (3) acceptability of program content, (4) acceptability and compliance with study questionnaires, and (5) attrition. Outcomes will be assessed at baseline, after the intervention, and 3 and 12 months postoperatively. We will conduct semistructured interviews alongside the RCT with 12 to 15 participants. Discussion: The proposed project will include the feasibility testing of an eHealth LSS prehabilitation program with potential to improve surgical outcomes. Results of this study will provide the foundation for future fully powered multicenter RCTs. Trial Registration: clinicaltrials.gov NCT05073081